The association of preoperative serum free fatty acid levels with survival in breast cancer patients - Liuran Li; Liang Jin; Lili You; Qiang Liu; Li Yan (Discover Oncology)
Abstract Background and objectives Serum free fatty acids (FFA) are associated with various types of cancer. However, the prognostic value of preoperative serum FFA levels and breast cancer (BC) remains unclear. This study aimed to elucidate the specific relationship between FFA levels and BC outcomes. Methods A retrospective review was conducted on 4133 patients with BC admitted to Sun Yat-sen Memorial Hospital from January 2015 to October 2021. Preoperative serum FFA levels were detected by the enzymatic endpoint method. The relationship between serum FFA levels and clinical characteristics was analyzed based on FFA interquartile range. Restricted cubic splines and multivariate Cox regression analyses were used to assess the relationship between preoperative serum FFA levels and overall survival (OS) in patients with BC. The hazard ratios (HRs) and 95% confidence intervals (95% CIs) were calculated. Results According to the FFA interquartile range, FFA levels were significantly correlated with OS (years) (p < 0.001). Restricted cubic spline analysis might reveal a U-shaped relationship between preoperative serum FFA levels and OS, after adjusting for other variables. According to the cutoff points for FFAs, multivariate Cox regression analyses showed that patients with low FFA levels (≤ 250 µmol/L) had higher rates of all-cause mortality and cancer-specific mortality than those with high FFA levels (530–700 µmol/L) in the total population and patients with a BMI of 18.5–24.0 kg/m2. A trend was observed indicating that elevated FFA levels (≥ 715 µmol/L) were associated with worse prognosis; however, this association failed to reach statistical significance. Conclusions There might be a nonlinear U-shaped relationship between preoperative serum FFA levels and survival in breast cancer patients, with lower FFA levels associated with worse OS. The effect of elevated FFA levels on prognosis requires further investigation.